A BOOK REVIEW: CHINA ON SCREEN: CINEMA AND NATION - G. M. Adhyanggono (Soegijapranata Catholic University, 2009)
This book examines some of the many and complex ways the national shapes and appears in Chinese films. The core argument of this book is twofold. First, the national informs almost every aspect of the Chinese cinematic image and narrative repertoire. Therefore, Chinese films-whether from China, Hong Kong, Taiwan, the diaspora, or understood as transnational-cannot be comprehended without reference to the national, and what are now retrospectively recognized as different Chinese cinematic traditions have played a crucial role in shaping and promulgating various depictions of the national and national identity. Second, as the challenge of locating Jackie Chan's Rumble in the Bronx and Rush Hour demonstrates that the national in Chinese cinema cannot be studied adequately using the old national cinemas approach, which took the national for granted as something known. Instead, the concept of national here needs to be approached as contested and construed in different ways. Therefore, it should be understood within an analytic approach that focuses on cinema and the national as a framework within which to consider a range of questions and issues about the national.